Kasalan [videorecording] weddings in the Philippines - Reyes, Jun
The Filipino wedding symbolizes not only the union of individuals but also the unity of the entire race. The film shows the mood of warmth, joy, kinship, generosity and spontaneity among the Filipinos in different wedding celebrations.